Satisfaction of Patients Family Reviewed from Caring Human Resources Psychiatic Poly in Hospital Muhammadiyah University of Malang - Hari Rachmawati; Sandu Siyoto; Nurdina Nurdina (Journal for Quality in Public Health, 2020)
Patient family satisfaction is the most important thing so that the hospital can develop. This can be created if medical personnel are able to provide good service. One indicator to support optimal service is to manage caring of appropriate human resources. Therefore, the purpose of this study was to determine the effect between caring human resources and family satisfaction of patients in Muhammadiyah University Hospital Malang. The study design used cross sectional. The sample of this study amounted to 110. This study used a random sampling stratification technique with research instruments using a questionnaire. In addition, the data analysis technique uses simple linear regression. Based on the data collection results obtained 108 respondents (98.2%) gave a good assessment of caring human resources, 2 respondents (1.8%) gave sufficient ratings, 79 respondents (71.8%) felt very satisfied, and 31 respondents (28.2%) were satisfied with the service at the hospital. Besides that simple linear test results show Sig. amounting to 0,000 (Sig. <0.05), which means that there is an influence of patient family satisfaction in poly psychiatry in terms of caring human resources as much as caring human resources affect the patient's family satisfaction by 15.7% (β = 0.157), and 84% others can be influenced or explained by other variables not included in this study. Based on these results it can be concluded that the management of good and appropriate caring of human resources will produce quality services that have a positive impact on the hospital by increasing patient family satisfaction and increasing number of visits because the hospital is considered appropriate and considered good in providing services